2013
DOI: 10.1093/hmg/dds555
|View full text |Cite
|
Sign up to set email alerts
|

Loci influencing blood pressure identified using a cardiovascular gene-centric array

Abstract: Blood pressure (BP) is a heritable determinant of risk for cardiovascular disease (CVD). To investigate genetic associations with systolic BP (SBP), diastolic BP (DBP), mean arterial pressure (MAP) and pulse pressure (PP), we genotyped ∼50 000 single-nucleotide polymorphisms (SNPs) that capture variation in ∼2100 candidate genes for cardiovascular phenotypes in 61 619 individuals of European ancestry from cohort studies in the USA and Europe. We identified novel associations between rs347591 and SBP (chromosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(60 citation statements)
references
References 62 publications
3
57
0
Order By: Relevance
“…These observations are further emphasised by a recent large-scale study genotyping approximately 50 000 SNPs in approximately 2100 genes, which revealed significant correlations between mRNA expression and the MDM4 SNP rs2169137 which is in linkage disequilibrium with rs4245739 SNP (Ganesh et al 2013).…”
Section: Discussionmentioning
confidence: 96%
“…These observations are further emphasised by a recent large-scale study genotyping approximately 50 000 SNPs in approximately 2100 genes, which revealed significant correlations between mRNA expression and the MDM4 SNP rs2169137 which is in linkage disequilibrium with rs4245739 SNP (Ganesh et al 2013).…”
Section: Discussionmentioning
confidence: 96%
“…Crucially, a genomic region containing ATP2B1, which encodes for PMCA1, has been identified as having a very strong association with BP variance and/or with hypertensive disease in different human population groups (Cho et al, 2009;Levy et al, 2009;Hong et al, 2010;Takeuchi et al, 2010;Johnson et al, 2011). Importantly, SNPs associating ATP2B1 with BP have attained genome wide significance in replication analyses in multiple different ethnic groups and have shown a consistently high level of genetic association (Tabara et al, 2010;Miyaki et al, 2012;Xi et al, 2012;Ganesh et al, 2013;Wang et al, 2013). SNPs relating to ATP2B1 in a Japanese cohort were found to give an odds ratio of 1.17 to 1.31 for hypertension (Tabara et al, 2010), a very similar level of risk as reported by other large scale GWAS.…”
Section: Plasma Membrane Calcium Atpase 1 Arterial Contractility Andmentioning
confidence: 99%
“…The largest GWAS effort to date involving participants of African origin was done by the Continental Origins and Genetic Epidemiology Network (COGENT) (Franceschini et al 2013). Discovery samples were obtained from 19 studies with an aggregate sample size of 29,000 individuals.…”
Section: Gwas Of Quantitative Bp Phenotypes In Diverse Populationsmentioning
confidence: 99%